The Role of Village Fancies in Community Empowerment at Nagari Salimpaung - Hikma, Aprila; Burhanuddin (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2025)
This research is motivated by various factors, including the need to understand how village mentoring acts as a facilitator, helping bridge the capacity gap between national policy and implementation at the village level, particularly in Nagari Salimpaung. This research is a field research study. The qualitative method employed a descriptive analysis approach, with data obtained through direct, in-depth interviews and supporting documentation.The results of this study reveal that village facilitators play a crucial role as facilitators in the community empowerment process in Nagari Salimpaung. This role has successfully increased community involvement in the planning, implementation, and evaluation stages of village development programs. First, the implementation of the community empowerment program in Nagari Salimpaung through village facilitation has resulted in increased capacity of Nagari institutions, strengthened the local economy, and improved the basic foundations that support community activities. Second, despite showing positive results, community empowerment in Nagari Salimpaung still faces several obstacles, including limited huma resources, minimal budget support, and the community's attitude toward change.